12.19: Experimental investigation on residual stresses in welded thick‐walled I‐shaped sections fabricated from Q460GJ structural steel plates. (13th September 2017) - Zhu, Qian; Nie, Shidong; Yang, Bo; Xiong, Gang; Dai, Guoxin
ABSTRACT: With the development of steel structures, a new type of high performance structural steel named by Q460GJ has been increasingly used in the modern steel constructions like the National Stadium of China in Beijing. Q460GJ structural steel is normally used in thick‐walled section members because of the favourable material properties, such as good weldability, low thickness effect on yield strength and low yield ratio. However, only limited knowledge is available on the residual stress distribution of thick‐walled section members fabricated from Q460GJ structural steel. Q460GJ structural steel has different mechanical characteristics and thermal properties from mild steel, both of which influence the formation of residual stress. This indicates that the available residual stress models of mild steel may not be appropriate for Q460GJ high performance steel. In this paper, residual stress in four thick‐walled welded H‐sections fabricated by Q460GJ structural steel were studied by experimental tests. Residual stress were measured by the sectioning method, and the variation of residual stress along steel plate thickness was then determined by slicing method. This study provides the magnitude and distribution of the longitudinal residual stress by both circular curve correction method and straightening measurement method. The effects on plate thickness and the interaction between flanges and webs are explored. Based on the statistical evaluation of the experimental results, a simplified multilayer residual stress model which is expected to use as initial imperfection in column analysis for residual stress in high performance steel is proposed.